Paternal Psychological Stress After Detection of Fetal Anomaly During Pregnancy. A Prospective Longitudinal Observational Study - Bekkhus, Mona; Oftedal, Aurora; Braithwaite, Elizabeth; Haugen, Guttorm; Kaasen, Anne (Frontiers in Psychology, 2020)
Background and Aims. Knowledge of carrying a fetus with a prenatal diagnosed anomaly may cause acute psychological stress to the parents. Most studies focus on maternal stress, yet fathers are often present at the ultrasound examinations and birth, and therefore may be affected similarly to the expectant mother. However, to date no existing studies have examined how detection of a fetal anomaly emotionally affects the expectant fathers throughout the pregnancy. Our aim was to longitudinally examine general health perceptions, social dysfunction and psychological distress in a subgroup of men where fetal anomaly was detected during pregnancy. Methods and Results. This study is part of the SOFUS study, a prospective, longitudinal, observational study. Participants were recruited when referred for an ultrasound examination conducted by a specialist in fetal medicine at Oslo University Hospital on suspicion of fetal malformation (study group). We examined differences between the men in the study group (N= 32) and a comparison group (N=83) on the General Health Questionnaire (GHQ), Impact of Event Scale (IES) and Edinburgh Postnatal Depression Scale (EDPS) across four time points in pregnancy. Results from repeated measured ANOVA suggests that depression decreased over time among men in both groups (η2=.15, p<.001). This effect was stronger in the study group, and differed from the comparison group (η2=.08, p<.001). There was also a main effect of time on IES scores, which decreased over time for both men in the study group and in the comparison group (η2=0.32, p<.001). That is, men in the study group were higher on IES, but this effect also decreased more in the study group than in the comparison group. Men in the study group and comparison group did not differ on perceived general health (GHQ: p=.864,). Conclusion: Results suggests that detection of a fetal anomaly has implications for paternal mental health during pregnancy. Expectant fathers scored higher on EPDS and IES than the comparison group in the acute phase after detection of fetal anomaly, thus there is impetus to provide psychological support for fathers, as well as mothers, at this difficult time.